Self-reconstructing Bessel beam created by two-photon-polymerized micro-axicon for light-sheet fluorescence microscopy - Li, Shufan (2021)
Observing micro-organisms with depth-resolving capability is important in optical microscopy for biomedical sciences and industries. We demonstrate the fabrication and use of a two-photon polymerized micro-axicon lens that generates a self-reconstructing pencil-like Bessel beam for light-sheet fluorescence microscopy (LSFM), providing 3D internal structures of micro-organisms. The fabricated SU-8 micro-axicon of 100 µm diameter transforms the input Gaussian beam from a single-mode fiber into a non-diffractive Bessel-Gauss beam. The focused spot size of the Bessel-Gauss beam is 2.3 ± 0.25 µm with a long propagation distance over 160 µm, which is well-suited for LSFM. The self-reconstruction capability of the generated Bessel-Gauss beam is investigated thoroughly through both simulations and experiments. Since this micro-axicon can be directly 3D-printed on single-mode fibers’ end facets or small mobile substrates, this can replace the bulky objective lens from conventional light-sheet microscopes. This will facilitate the wide-spread use of 3D tomographic imaging of micro-organisms, especially in compact micro-fluidic devices and lab-on-a-chip architectures.